Analysis of Students' Design Thinking in Creating 3D Creative Works Utilizing Mobile Technology within the Framework of Local Wisdom - Raden Fanny Printi Ardi; Muhammad Roil Bilad; Hisbulloh Als Mustofa; Adam Bachtiar Maulachela (Faculty of Engineering and Applied Science, 2024)
This study investigated students' design thinking in creating 3D creative works using mobile technology in the framework of local wisdom. By employing a mixed-methods approach, the study compares the design thinking abilities of students who engaged with mobile technology in the context of local wisdom with those who donot. Quantitative analysis, involving sixty students, revealed that the experimental group, exposed to mobile technology and local wisdom, demonstrated significantly higher competencies in design thinking, particularly in areas such as comfort with uncertainty, human-centeredness, and collaborative work. Qualitative insights further illuminated the enriched learning experience, showcasing students' deepened engagement and connection to cultural heritage through the integration of local wisdom into their 3D creative projects. The findings underscore the pivotal role of mobile technology and local wisdom in fostering innovative design thinking, suggesting that this approach not only facilitates creative problem-solving but also instills a sense of cultural identity and pride among students. Despite its focused educational context and limited sample size, the study suggested broader implications for curriculum development, recommending the incorporation of these elements into design and creative courses to enhance students’ design skills and cultural understanding.